EMPLOYEE ENGAGEMENT AND BEHAVIOR IMPACT ON PERFORMANCE WITH WORK-LIFE BALANCE MEDIATION - Rahmawati, Dyah; Herlambang, Toni; Sanosra, Abadi (Manager : Jurnal Ilmu Manajemen, 2024)
This study aims to examine the effects of employee engagement and work behavior on the performance of employees at the Department of Education in Jember Regency, with work-life balance serving as a mediating variable. The research population includes all employees of the Department of Education in Jember Regency, with a sample size of 115 respondents. Data were collected through questionnaires and analyzed using Warp PLS software. The findings indicate that both employee engagement and work behavior positively and significantly influence work-life balance. In turn, work-life balance positively and significantly affects employee performance. Additionally, work-life balance serves as a significant mediating variable in the relationship between employee engagement, work behavior, and employee performance. These results underscore the importance of employee engagement and work behavior in fostering a balance between work and personal life, which ultimately enhances employee performance. The practical implications of this study highlight the need for programs that support employee engagement and positive work behavior to strengthen work-life balance, thereby contributing to improved employee performance at the Department of Education in Jember Regency.